Idempotent Cayley Graph of the Ring (Z_n,⊕,⊙) - Levaku, Madhavi; Anand, Seetaka; Thejeswini, Ramya (European Journal of Applied Sciences, 2025)
The idempotent Cayley graph of the ring is the Cayley graph associated with the symmetric set consisting of idempotent elements and their inverses in the group . In this paper, we derive some basic properties of the idempotent elements and construct the idempotent Cayley graph. It is shown that this graph is connected and Hamiltonian. Further, if , this graph is bipartite.